2007
DOI: 10.1038/nprot.2007.371
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of cell therapy and assessment of cardiac function using magnetic resonance imaging in a mouse model of myocardial infarction

Abstract: We have developed a mouse severe combined immunodeficient (SCID) model of myocardial infarction based on permanent coronary artery occlusion that allows long-term functional analysis of engrafted human embryonic stem cell-derived cardiomyocytes, genetically marked with green fluorescent protein (GFP), in the mouse heart. We describe methods for delivery of dissociated cardiomyocytes to the left ventricle that minimize scar formation and visualization and validation of the identity of the engrafted cells using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…In that recently published study, 2 we injected cardiomyocyteenriched differentiated hESCs into uninjured and acutely infarcted hearts of immunodeficient NOD-SCID mice and performed a longitudinal follow-up of cardiac function by MRI. 3 Like Laflamme et al, we found that hESC-CMs survived selectively and improved heart function 4 weeks after myocardial infarction when compared to noncardiac differentiated derivatives of hESCs. 2 However, at the 12-week time point, cardiac function was not improved compared to the control animals, 2 even though only cardiomyocytes had formed a substantial graft in the infarcted heart ( We quantified graft size based on a semiquantitative scaling (scale from 0 to 13) based on green fluorescent protein (GFP) fluorescence in the whole heart by a blinded investigator.…”
mentioning
confidence: 69%
“…In that recently published study, 2 we injected cardiomyocyteenriched differentiated hESCs into uninjured and acutely infarcted hearts of immunodeficient NOD-SCID mice and performed a longitudinal follow-up of cardiac function by MRI. 3 Like Laflamme et al, we found that hESC-CMs survived selectively and improved heart function 4 weeks after myocardial infarction when compared to noncardiac differentiated derivatives of hESCs. 2 However, at the 12-week time point, cardiac function was not improved compared to the control animals, 2 even though only cardiomyocytes had formed a substantial graft in the infarcted heart ( We quantified graft size based on a semiquantitative scaling (scale from 0 to 13) based on green fluorescent protein (GFP) fluorescence in the whole heart by a blinded investigator.…”
mentioning
confidence: 69%
“…Tissue engineering [58][59][60] or intramyocardial injection of combinations of cell types seem more appropriate than intracoronary injection of single cell suspensions since the latter may not pass the endothelial barrier and may cause micro-infarctions 61 ,but much more research is needed before clinical strategies can be properly defi ned. In general, the present discrepancy between mid-and long term results and the dependence of outcome on the particular control taken argues for careful re-evaluation of reported improvements by any cell type 62 .…”
Section: Optimizing Cell-based Therapy For Heart Repairmentioning
confidence: 99%
“…hESCs can be efficiently induced to form cardiomyocytes (hESCCMs), facilitating the dissection of the gene activation events that underpin this process, which, in turn, could lead to the identification of new candidate genes for congenital heart defects (Passier and Mummery, 2005). However, the transplantation of such hESC-CMs into infarcted rodent hearts has yielded disappointing functional improvements (van Laake et al, 2007;van Laake et al, 2008).…”
Section: Stem Cells and Regenerationmentioning
confidence: 99%